Stereotip dan Konflik Antar Suporter Sepakbola Persibat dan Persip Pekalongan - Erik Bagus Prastyawan; Fajar Junaedi (UMSU, 2018)
Football supporters or fans are spirit for football clubs and even become an identity of the city itself. The rivalry of an Indonesian football club supporters are the social phenomenon. In a north coast region of Middle Java Province, recently there is a conflict and clashes between Persibat Batang football supporters and Persip Pekalongan football supporters. The conflict between football supporters from both clubs culminated on April 27, 2017 when the two teams were met in the level and the same group in second league Indonesia. Till now, there is still friction between both of them. So here the researcher then examines from the point of view of a phenomenon of conflict between the two that creates stereotypes and an identity of a group in it which aims to find and describe the factors of the beginning of the rivalry between the two supporters. Researchers used a qualitative approach method and the research data was descriptive data with a case study strategy in order to capture the phenomena in the field, while the data analysis used interactive analysis.This study found that a supporter conflict due to rivalry and excessive fanaticism, then stereotypes emerged and formed because of differences in groups between the two who fight each other, while the identity in the group is no longer viewed, who is considered different from the group is his enemy. Finally, the identity between football supporters are relational.